Problems encountered with hearing aids in adult population - Kenar, Fethullah; Ali Babademez, Mehmet (ENT Updates, 2015)
Language and speech are natural tools for communication. Loss of hearing causes multiple problems, results in a decrease in life quality and psychosocial regression, depressive symptoms and communication failures. For situations when medical and/or surgical approaches to eliminate or reduce the effects of hearing loss do not succeed, hearing aid devices are an option. The aim of this paper is to determine the problems with usage of hearing aids by adults and to offer possible solutions. The selection of the type and model of a hearing aid device in a way to meet individual requirements is a critical step. An efficient hearing aid application is expected to be more beneficial when supported by an audiological rehabilitation. The problems encountered in usage of hearing devices in adult stage are not only physical factors but can also be individual factors. Lately the digital hearing devices are gaining popularity and utilisation problems are encountered quite less but still many problems are waiting to be solved. To minimise the problems encountered with usage of hearing aids in society, healthcare professionals advising hearing aids should have a better training and equipment, number of disciplines focusing on hearing devices should be increased and all related parties (government agencies, healthcare workers advising hearing aid devices, device suppliers) should follow developments in the field closely. It is expected for all the parties to find a common ground and aim for maximum benefit from the audiological rehabilitation of individuals with hearing loss.